Analisis Peranan Pusat Pelatihan Pertanian dan Pedesaan Swadaya (P4S) Manunggal Tani dalam Pemberdayaan Petani di Desa Bero Kecamatan Trucuk Kabupaten Klaten - Pravitasari, Erlin Dara; Wibowo, Agung; Widiyanto, Widiyanto (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
The problem in the world of agriculture today is that farmers are still dependent on government assistance. One of the affected villages is Bero Village. The problem is that farmers are still dependent on government assistance, so they need the education to increase their resources and don't depend on the government. The strategy taken to overcome the problem is to hold a farmer empowerment program. The extension group involved in the empowerment activities is the non-governmental organization P4S Manunggal Tani. This study was conducted to determine the role of P4S Manunggal Tani on farmer empowerment and the impact of farmer empowerment on self-reliance. The research method used in this research is qualitative with a descriptive approach. The location of this research is the non-governmental organization P4S Manunggal Tani located in Bero Village, Trucuk District, Klaten Regency. The study was conducted from December 2020 – July 2021. The method of determining the informants of this research was using purposive and snowball sampling. Testing the validity of this research data are using triangulation methods and triangulation sources. The results showed that the role of P4S Manunggal Tani in empowering farmers in Bero Village are training, counseling, farmer regeneration, and network development. This empowerment activity impacted increasing the human resources of farmers, and farmers are independent by not depending on the government, which is characterized by being able to produce their organic fertilizers. Organic fertilizer is one of the ingredients to keep rice fields fertile. It needs education for farmers regarding the basics of agricultural science for the